2015
DOI: 10.4018/978-1-4666-7521-6.ch009
|View full text |Cite
|
Sign up to set email alerts
|

Changing Consumption Patterns in Green Economy

Abstract: This chapter has considered the recent changes occurring in consumer habits, aiming to highlight the link between them and the transition to a green economy. In the first part, after a brief introduction, the authors perform a review of the literature in the field, starting from the presentation of the concept of sustainable consumption. They start with the major changes in the social current economic environment and their impact on changes of the consumption patterns; they continue with the presentation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…As the role of information and communication technologies in the purchasing process grows steadily, customer expectations also increase, forcing traders to react quickly to market movements [32,33]. Since the beginning of the Industry 4.0 era, researchers have predicted dramatic changes in the way of interaction between consumers and retailers, driven by the global use of new technologies and the imminent emergence of new efficient retail business models [34].…”
Section: Marketing In the Industry 40 Stagementioning
confidence: 99%
“…As the role of information and communication technologies in the purchasing process grows steadily, customer expectations also increase, forcing traders to react quickly to market movements [32,33]. Since the beginning of the Industry 4.0 era, researchers have predicted dramatic changes in the way of interaction between consumers and retailers, driven by the global use of new technologies and the imminent emergence of new efficient retail business models [34].…”
Section: Marketing In the Industry 40 Stagementioning
confidence: 99%
“…Thus, it is influenced by the change in the agricultural paradigm (Andrei, Mieilă and Panait, 2017;Sima and Gheorghe, 2015), the land grabbing (Ciutacu, Chivu and Andrei, 2017) or the volatility of agri-food prices (Andrei et al, 2016 Zanin et al (2017) also found that food security is a critical component in ensuring the sustainable development of contemporary economies, and any problem triggered within a certain state has a contagion effect, propagating in the case of other states as well. The need to ensure food safety standards is important for all products, whether of animal or vegetal origin or industrially processed, regardless of the production process, the distribution chain or their addressability (Post, 2006;Aoki, 2011;Strauss, 2014).…”
Section: Review Of the Scientific Literaturementioning
confidence: 99%
“…Horizontal priorities linking these sectors are transported in the region, support for investment and entrepreneurial spirit, the region's human resources (which are increasingly depleted) and a healthy environment (Ilić, B., 2016). Development can be achieved by sustainable consumption (Sima & Gheorghe, 2015) and country of origin serves as a very important basis for this consumption (Šapić et al, 2018). All that that require an integrated approach to the social, economic, environmental, and technological environment (Nica et al, 2018).…”
Section: Timok Region -General Characteristics and Tourism Potentialmentioning
confidence: 99%